End of the line for the golden lion tamarin? A single road threatens 30 years of conservation efforts - Ascensao, Fernando; Niebuhr, Bernardo B. [UNESP]; Moraes, Andreia M. [UNESP]; Alexandre, Brenda R.; Assis, Julia C. [UNESP]; Alves-Eigenheer, Milene A. [UNESP]; Ribeiro, John W. [UNESP]; Morais Jr, Marcio M. de; Martins, Andreia F.; Oliveira, Ademilson; Moraes, Elisama; Ramos, Jadir H.; et al. (Wiley-Blackwell, 2019)
Roads have a myriad of negative effects on biodiversity, ultimately threatening the persistence of populations. In this Perspective we call attention to an extreme example, where the entire current geographic range of the endangered golden lion tamarin (Leontopithecus rosalia, GLT) is bisected by a major highway that is being widened to four lanes. We believe that the planned mitigation actions are not enough to reduce the expected increase of barrier effects and road mortality. These impacts may lead to a sequence of cascading effects that could jeopardize the conservation actions that prevented the extinction of GLTs three decades ago. We identify specific road sections along the highway and accompanying paved roads in the region that if equipped with tailored over passages would greatly reduce the road barrier effects. We also highlight areas where reforestation efforts could be extended in order to help reestablishing the connectivity between GLT habitat areas. We suggest that the working group integrating key decision makers and stakeholders, including the Non-governmental organization leading the conservation efforts, partner universities, national road and environmental agencies, and the road construction company, to implement and to monitor the complementary road passages to improve connectivity of GLT habitat, and consequently to ensure the species' survival.
Keywords: endangered species; habitat fragmentation; landscape connectivity; mitigation prioritization; roadkill